Pengembangan strategis produk gadai emas di bank syariah: peluang, tantangan, dan inovasi strategis - Rahma, Vellan Zunia (Maliki Interdisciplinary Journal, 2025)
This study examines the strategic development of gold pawn (rahn) products in Islamic banking institutions in Indonesia, emphasizing opportunities, challenges, and innovative strategies. Using insights from five national journals— (Mahdania et al., 2025), (Amri & Iqbal, 2025), (Pratiwi, 2019) , (Pramadeka et al., 2024), and (Barri, 2019) —this paper analyzes how Islamic banks manage product innovation to sustain competitiveness while adhering to Sharia principles. Gold pawn products play an essential role in supporting customer liquidity, promoting financial inclusion, and strengthening ethical finance. The study finds that digitalization, hybrid contracts, and marketing innovation are core strategies that enhance customer reach and operational efficiency. However, regulatory complexity, customer literacy gaps, and operational costs remain significant challenges. Islamic banks must, therefore, align technological transformation with Sharia governance to ensure transparency and compliance. Furthermore, partnerships with gold retailers and fintech institutions can foster market expansion and increase customer trust. This study contributes to the understanding of strategic management within Islamic banking by highlighting the importance of innovation and ethical integrity in gold pawn services as a sustainable and Sharia-compliant financial solution.